Web Link Classification And Aceessibillity Modelling For Web Security Enhancement - Chong, Chee Way (1999)
The main objective of this research is to analyse the internal behaviour of WWW with regard to web link design, web link structural organisation, web link accessibility and web surfing efficiency, and to recommend solution models for improving the quality of WWW and for enhancing the web security. A new method for identifying the independent set of links in a web link network is proposed. If the links in an independent set satisfy te equivalence relation, an equivalence class is formed. Considering the vagueness of link accessibility, fuzzy c-mean algorithm is utilised to classify the web links into five linguistic accessibility clusters. Fuzzy equivalence classes are identified if the links satisfy fuzzy equivalence relation. The formation of a fuzzy equivalence class implies that direct accessibility of its elements is consistent and strong. Multiple link structures are analysed and their accessibility functions are derived by using both probabilistic and fuzzy concepts. The importance of the subsets of links in each of these structures is evaluated by using Birnbaum's measure and their implicit features are investigated. State space models for partial accessibility of subsets of links are also developed by using both probabilistic and fuzzy concepts. A Monte Carlo simulation model is developed by assuming an exponentially decreasing losing rate. Identifying the presence of minimal cut sets on a web link network is then considered to enhance the reliability and security of the web site. To impose link level security on different authorised users, a link level access control mechanism ( LiBAC) is proposed to categorise and limit the users for accessing the web links by providing partial access states. New navigation models, termed as pre-order and Hamiltonian models are proposed for naïve users to improve their surfing efficiency. Fuzzy distance measure is utilised to identify the optimal path that leads to a pre-defined target page.